Strategies of Remedial Programs in Improving Qur'anic Literacy at Bumrungsuksa Islamic Boarding School - Ina Zainah Nasution; Rindi Irma Audia (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to analyze the strategies of remedial programs in improving Qur'anic literacy at Bumrungsuksa Islamic Boarding School. The research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving teachers and students as research participants. The findings reveal that remedial program strategies are implemented through grouping students based on their ability levels, applying various instructional methods such as talaqqi, tahsin, and intensive repetition, as well as providing individual guidance. The remedial program has proven to significantly improve students' ability to read and write the Qur'an. However, several challenges were identified, including limited instructional time and differences in students’ initial abilities. Therefore, sustainable strategies and continuous teacher professional development are required to optimize the effectiveness of remedial programs.